Optimalisasi Manajemen Waktu dan Pengembangan Diri Sebagai Kunci Peningkatan Kinerja Pegawai - Neks Triani (Amsir Management Journal, 2026)
Time management and self-development are examined as determinants of employee performance in a hospital setting. The study aims to identify the partial and joint effects of time management and self-development on employee performance and to estimate the proportion of variance in performance explained by these two factors. A descriptive analytical approach is employed, incorporating validity and reliability testing, multiple linear regression, partial significance testing, simultaneous significance testing, and the coefficient of determination. Primary data are collected through structured questionnaires administered to hospital employees. The findings show that time management has a statistically significant partial effect on employee performance, indicating that employees who manage their time more effectively tend to achieve higher performance levels. Self-development also demonstrates a highly significant partial effect on performance, suggesting that continuous efforts to improve skills and competencies are closely associated with better work outcomes. When considered together, time management and self-development exert a significant joint influence on employee performance, confirming that these variables interact to enhance overall effectiveness at work. Regression analysis further reveals that time management and self-development have a moderately strong relationship with employee performance, with the coefficient of determination indicating that a meaningful portion of performance variation can be explained by these two factors.